NOBODY'S BOY: An Analysis of Hero Character and The Constellation of Characters in a Bildungsroman Novel - Ray Sugar, - (2011)
The present study attempts to disclose 1) how the hero character is developed in the novel Nobody's Boy written by Hector Malot; and 2) the constellation of characters that appear in the novel. Thus, this study focuses on the narrative structure analysis of the novel as a Bildungsroman novel. This research employs close reading strategy in where the novel is re-read thoroughly and carefully to determine the main issue of the study and to collect the data. Afterwards, the data collected in the form of textual evidences is analyzed within Nikolajeva's framework on hero development and the constellation of characters in children's literature. Moreover, Bakhtin's notion on Bildungsroman as realist genre helps the analysis of the novel's narrative structure. The result of the study indicate that the hero character developed through several significant narrative events such as children is placed in an extraordinary situation, the character crosses some form of the "threshold", the character quests his identity, the character meets friends or an opponent of the opposite sex, atonement with the real parents, and going back to an ordinary life. This study suggests that there is a close relation between hero development and constellation of characters in developing the hero in children's literature.